Acute Effects of Complex Conditioning Activities on Athletic Performance and Achilles Tendon Stiffness in Male Basketball Players - Papla, Monika; Ewertowska, Paulina; Krzysztofik, Michał (Journal of sports science & medicine, 2023)
The goal of this study was to compare the effects of a bilateral conditioning activity consisting of back squats and drop jumps with a unilateral one consisting of split squats and depth jumps to lateral hop over sequentially performed countermovement jump (CMJ), modified t-agility test (MAT), and Achilles tendon stiffness. Twenty-six basketball players participated in this study and were randomly and equally assigned to one of two different test groups: bilateral (B - CA) or unilateral (U - CA) conditioning activity group. The B - CA group completed 2 sets of 4 repetitions of back squats at 80% of one-repetition maximum (1RM), then 10 drop jumps, while the U - CA group performed 2 sets of 2 repetitions of split squats on each leg at 80%1RM, followed by 5 depth jumps to lateral hop on each leg as conditioning activity (CA) complexes. After a warm-up and 5 min before the CA the baseline Achilles tendon stiffness, CMJ, and MAT time measurement were performed. In the 6th min after the CA, all tests were re-tested in the same order. The two-way repeated measures mixed ANOVAs revealed that both B - CA and U - CA failed to produce significant improvements in CMJ and MAT performance. In addition, a significant increase in Achilles stiffness was demonstrated with both protocols (a main effect of time: p = 0.017; effect size = 0.47; medium). This study revealed that combining back squats and drop jumps, as well as split squats and depth jumps to a lateral hop, had no effect on subsequent CMJ and MAT performance in basketball players. Based on these results, it can be assumed that combinations of exercises, even if they have similar movement patterns, may cause excessive fatigue, resulting in no PAPE effect.
Keywords: sportovní výkon; Achillova šlacha; Post-activation performance enhancement; change of direction; countermovement jump; Athletic Performance; postura těla; Basketball; Exercise; Humans; mužské pohlaví; Male; lidé; basketbal; cvičení; PAPE; Achilles Tendon; Posture